Pengaruh Desain Produk dan Harga Terhadap Keputusan Pembelian Pada Brand Rucas di Instagram - Achmad Ramadhan; Ita Rahmawati (Business and Economic Publication, 2026)
This study aims to examine how product design and pricing influence consumer purchasing decisions related to the Rucas brand on Instagram, given the increasingly fierce competition in the local fashion sector. The uniqueness of this study lies in its emphasis on the local brand Rucas, which largely uses Instagram for marketing, a topic that has not been widely explored through empirical studies. This study uses an associative quantitative method with a purposive sampling technique involving 100 respondents who have purchased Rucas products in the past year. Data were collected using a 1-5 Likert scale questionnaire and analyzed through multiple linear regression using SPSS 27. The results showed that product design had a positive and significant effect on purchasing decisions (t = 5.574; p < 0.001), price had a positive and significant effect on purchasing decisions (t = 7.687; p < 0.001). Simultaneously, product design and price had a significant effect on purchasing decisions with an F value of 111.160 and a coefficient of determination (R²) of 0.696. These findings indicate that Rucas consumers on Instagram consider visual aspects of product design and affordability in their purchasing decisions. This research contributes to the development of digital marketing studies and consumer behavior in the local social media-based fashion industry.